2017
DOI: 10.1002/biot.201700073
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibrous Meshes Cultured With Wharton's Jelly Stem Cell: An Alternative for Cartilage Regeneration, Without the Need of Growth Factors

Abstract: Many efforts are being directed worldwide to the treatment of OA-focal lesions. The majority of those efforts comprise either the refinement of surgical techniques or combinations of biomaterials with various autologous cells. Herein, we tested electrospun polycaprolactone (PCL) nanofibrous meshes for cartilage tissue engineering. For that, articular chondrocytes (hACs) isolated from human osteoarthritic joints and Wharton's Jelly Stem Cells (hWJSCs) are cultured on electrospun nanofiber meshes, without adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…43,44 Four studies reported the induction of HWJSC differentiation by culturing these cells on inductive substrates without the need for conditioning media. [45][46][47][48] The results were positive in terms of gene expression, morphological changes, and phosphatase alkaline activity. Interestingly, the biomaterials used for this purpose were based on calcium phosphate in two cases, 45,48 electrospun polycaprolactone (PCL) nanofiber meshes in one case, 46 and polyacrylamide hydrogels in one other case, 47 and some authors conclude that the differentiation efficiency may vary depending on the substrate stiffness.…”
Section: Mesodermal Differentiation Potential Of Hwjscmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Four studies reported the induction of HWJSC differentiation by culturing these cells on inductive substrates without the need for conditioning media. [45][46][47][48] The results were positive in terms of gene expression, morphological changes, and phosphatase alkaline activity. Interestingly, the biomaterials used for this purpose were based on calcium phosphate in two cases, 45,48 electrospun polycaprolactone (PCL) nanofiber meshes in one case, 46 and polyacrylamide hydrogels in one other case, 47 and some authors conclude that the differentiation efficiency may vary depending on the substrate stiffness.…”
Section: Mesodermal Differentiation Potential Of Hwjscmentioning
confidence: 99%
“…[45][46][47][48] The results were positive in terms of gene expression, morphological changes, and phosphatase alkaline activity. Interestingly, the biomaterials used for this purpose were based on calcium phosphate in two cases, 45,48 electrospun polycaprolactone (PCL) nanofiber meshes in one case, 46 and polyacrylamide hydrogels in one other case, 47 and some authors conclude that the differentiation efficiency may vary depending on the substrate stiffness. 47 Finally, nine studies combined the differentiation potential of conditioning media and biomaterials to increase the efficiency of the differentiation process.…”
Section: Mesodermal Differentiation Potential Of Hwjscmentioning
confidence: 99%
“…Several PEG hydrogels in combination with several other polymers are under investigation for repairing cartilage defects [ 264 , 265 ]. Combinations of alginate, gellan, and type II collagen have all been printed into complex cartilage constructs and showed good biocompatibility and enhanced chondrocyte proliferation [ 37 , 258 , 264 267 ].…”
Section: 3d Bioprinting Of Tissuesmentioning
confidence: 99%
“…These strategies are aimed at changing the tissue environment by the introduction of exogenous material and biological factors with the sole aim of accelerating and improving the body's healing process. Materials and biomimetics of the extracellular matrix have been in use for several years now and do more than just providing the physical structure [ 37 39 ]. Materials and biomimetics can stimulate regeneration on their own but can also be used to present biomolecules such as growth factors to promote the growth of cells [ 32 , 34 , 38 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two papers focus on the differentiation induction to neural cells using a medium containing small molecule inhibitors and growth factors, and hydrogels . Other two papers deal with the differentiation to chondrocytes using electrospun fibers and poly(vinylalcohol)‐based membrane immobilizing peptide ligands . One interesting work is an application of mesenchymal stem cells for the treatment of abdominal defects .…”
mentioning
confidence: 99%